Queen's Park Hotel, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
The Queen's Park Hotel, located in Port of Spain on the southern side of the Queen's Park Savannah, was first opened in January 1895. In the foreground, cattle can be seen grazing in the Queen's Park Savannah. Postcard number 8919.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Savannas--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Cattle--Trinidad and Tobago; [1930]; Historic hotels--Trinidad and Tobago; Hotels--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Trees--Trinidad and Tobago; Architecture--Trinidad and Tobago; Roads--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago; Scenic overlooks--Trinidad and Tobago; Open spaces--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)